2002
DOI: 10.1002/j.1467-8438.2002.tb00484.x
|View full text |Cite
|
Sign up to set email alerts
|

Family Constellation — A Therapy Beyond Words

Abstract: Family Constellation, a psychotherapeutic approach associated with the name Bert Hellinger, has become a popular yet also controversial form of systemic therapy in the German‐speaking therapy community. ‘Family Constellation’ (Familienstellen) means the individual client's physical‐emotional positioning and re‐positioning of substitute family members in relation to each other, with help of a therapeutic group. Family Constellation is a one‐session approach that addresses family‐of‐origin issues. The therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
19
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 3 publications
1
19
0
4
Order By: Relevance
“…Issues relating to perpetrators, trauma and healing (Carnabucci & Anderson, 2012) were further significant topics. CW is acknowledged in organisational contexts and emphasised in international CW literature (Birkenkrahe, 2008;Stiefel et al, 2002).The study also confirmed that apartheid, race, racialised identities, relationships between perpetrator and victim, and sexual abuse and violence/crime (Payne, 2005) are important themes across cultural groups in CW. Culture and the cultural context (Dykstra, 2004) are viewed as influencing healing and constellations.…”
supporting
confidence: 63%
See 3 more Smart Citations
“…Issues relating to perpetrators, trauma and healing (Carnabucci & Anderson, 2012) were further significant topics. CW is acknowledged in organisational contexts and emphasised in international CW literature (Birkenkrahe, 2008;Stiefel et al, 2002).The study also confirmed that apartheid, race, racialised identities, relationships between perpetrator and victim, and sexual abuse and violence/crime (Payne, 2005) are important themes across cultural groups in CW. Culture and the cultural context (Dykstra, 2004) are viewed as influencing healing and constellations.…”
supporting
confidence: 63%
“…Others (Ruppert, 2000;Weber, 1994) focus on symptoms, psychiatric disorders, disability, infertility victimisation, perpetration of war crimes, fostering, adoption and couple problems. Carnabucci and Anderson (2012) discuss perpetrators, justice, trauma and healing as topics in CW whilst Stiefel et al (2002) use it in organisational settings and Birkenkrahe (2008) for business-related solutions. For South Africa, Payne (2005) highlights that CW is an intervention to deal with the individual, the family and the ethnic conscience of apartheid, by focusing on relationships of victims and perpetrators, government and regimes, war, sexual abuse and crime.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…As in Europe (Stiefel et al, 2002), CW has gained interest on a practical level within South African contexts.…”
Section: Discussionmentioning
confidence: 99%